Proceedings of the Social and Humanities Research Symposium (SORES 2020) 2021
DOI: 10.2991/assehr.k.210617.023
|View full text |Cite
|
Sign up to set email alerts
|

Political Connections, Financing and Dividend Policy

Abstract: The purpose of this study is to see the political connections DER, EPS, SIZE, growth and ROA influence on the company's dividend distribution policy. The sample in the study SOE listed on the Indonesia Stock Exchange in 2010-2018 period. The sample was selected using purposive sampling technique and obtained 12 companies. This study uses a quantitative approach with analysis tools using multiple linear regression with the help of EViews 9.0 software. The results of this study indicate that political connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Petry et al [5] found that plastic bags were the predominant form of waste among 50 stranded sea turtles, underscoring the severity of oceanic plastic pollution. Scientific evidence indicates that despite the implementation of plastic waste reduction programs, such as discontinuing the use of single-use plastic bags in restaurants, retail stores, and supermarkets, and introducing paid plastic bag programs in large cities [6][7], plastic bags (specifically, those made from polyethylene) continue to be the predominant component of plastic waste composition [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Petry et al [5] found that plastic bags were the predominant form of waste among 50 stranded sea turtles, underscoring the severity of oceanic plastic pollution. Scientific evidence indicates that despite the implementation of plastic waste reduction programs, such as discontinuing the use of single-use plastic bags in restaurants, retail stores, and supermarkets, and introducing paid plastic bag programs in large cities [6][7], plastic bags (specifically, those made from polyethylene) continue to be the predominant component of plastic waste composition [8][9][10].…”
Section: Introductionmentioning
confidence: 99%